Isolation and Structural Characterization of Alkali and Alkaline Earth Metal Salts with Synthetic Non Cyclic Ionophores - Poonam Hariyani; Rekha Vijay; Loni Lokwani; Uma Sharma (Journal of Sciences, Islamic Republic of Iran)
In the present study, an investigation on the complex formation between mono- and divalent metal ions (Na+, K+, Li+ and Mg2+) in the form of salt with different podands using various solvents has been carried out.  Isolated complexes were characterized by different spectroscopic techniques viz. IR, NMR and elemental analysis. On the basis of the obtained data, it was observed that number of donor sites, ionic potential, size fit concept in pseudocyclic cavity etc. are the deciding factors for complexation which make it differ between solid and solution complexation using ionophores.